Health Workforce Maldistribution and Physician Migration: Challenges to Rural Healthcare Access in Eastern Indonesia - Yuningsih, Siti Hadiaty; Surya, Dhika (International Journal of Health, Medicine, and Sports, 2025)
Indonesia, the world's largest archipelagic nation, faces long-standing inequality in the distribution of healthcare workers, particularly in its eastern regions such as Papua, Maluku, and East Nusa Tenggara. This study investigates the structural causes of health workforce maldistribution and the limited success of physician retention programs over the last decade. Using a descriptive qualitative approach, the study combines a systematic literature review, policy document analysis, and secondary data evaluation, including findings from recent Discrete Choice Experiments (DCE) involving over 500 physicians. Results reveal that despite government programs like Nusantara Sehat and mandatory rural service, the national ratio of healthcare workers (3.84 per 1,000 population) remains below the WHO standard for Universal Health Coverage (UHC), and retention in remote areas is still critically low (<25% after two years). Regional disparities persist, with Papua and NTT suffering from the highest shortages up to 48% of community health centers lack doctors. The DCE findings confirm that non-monetary factors such as guaranteed safety, adequate hospital infrastructure, career development opportunities, and legal housing significantly influence physician retention, more so than financial incentives alone. Policy interventions remain fragmented and overly reliant on temporary placement incentives, without addressing systemic issues such as geographic isolation, weak intersectoral coordination, and limited rural training pathways. In response, the study recommends a shift toward holistic, long-term solutions, including CBME-based medical education, integrated specialist training in remote areas, expanded telemedicine capacity, and real-time health workforce planning systems. Addressing the maldistribution of healthcare workers is vital not only for equity in health access but also for national development. With coordinated, evidence-based policy reform, Indonesia has the potential to strengthen rural healthcare systems and accelerate progress toward its 2030 SDG and UHC targets.